2016
DOI: 10.1021/jacs.6b03373
|View full text |Cite
|
Sign up to set email alerts
|

Diverted Total Synthesis of Promysalin Analogs Demonstrates That an Iron-Binding Motif Is Responsible for Its Narrow-Spectrum Antibacterial Activity

Abstract: Promysalin is a species-specific Pseudomonad metabolite with unique bioactivity. To better understand the mode of action of this natural product, we synthesized 16 analogs utilizing diverted total synthesis (DTS). Our analog studies revealed that the bioactivity of promysalin is sensitive to changes within its hydrogen bond network whereby alteration has drastic biological consequences. The DTS library not only yielded three analogs that retained potency but also provided insights that resulted in the identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 26 publications
0
52
0
4
Order By: Relevance
“…Thetotal synthesis of promysalin (88)and as eries of analogues have recently been reported and their antimicrobial activities evaluated. [168][169][170][171] In Gram-positive bacteria, such as Staphylococcus aureus, transport systems for essential metal ions typically rely on substrate-binding proteins (SBP) and an ABC transporter (Figure 1). TheM n 2+ uptake system comprising the SBP MntC and the membrane importer MntB is essential in S. aureus,a sM n 2+ is ac ofactor of enzymes involved in the detoxification of reactive oxygen species.Until now,nosmallmolecule inhibitors of this pathway have been described, but an antibody fragment was developed which complexes MntC and prevents its interaction with MntB.…”
Section: Siderophore Quenchingmentioning
confidence: 99%
“…Thetotal synthesis of promysalin (88)and as eries of analogues have recently been reported and their antimicrobial activities evaluated. [168][169][170][171] In Gram-positive bacteria, such as Staphylococcus aureus, transport systems for essential metal ions typically rely on substrate-binding proteins (SBP) and an ABC transporter (Figure 1). TheM n 2+ uptake system comprising the SBP MntC and the membrane importer MntB is essential in S. aureus,a sM n 2+ is ac ofactor of enzymes involved in the detoxification of reactive oxygen species.Until now,nosmallmolecule inhibitors of this pathway have been described, but an antibody fragment was developed which complexes MntC and prevents its interaction with MntB.…”
Section: Siderophore Quenchingmentioning
confidence: 99%
“…In this context, promysalin, a salicylate-containing Pseudomonas putida antibiotic, was described to selectively target members of the genus Pseudomonas , without affecting the viability of other Gram-negative and Gram-positive bacteria 4 , 5 . More recently 6 , diverted total synthesis of promisalyn analogs demonstrates that the bioactivity of the molecule is sensitive to changes within its hydrogen bond network. Furthermore, it was reported that promysalin inhibits the production of the siderophore pyoverdine which is often linked to virulence.…”
Section: Introductionmentioning
confidence: 99%
“…13 Both Danishefsky and Myers have beautifully applied DTS to the development of novel anticancer 14 and antibiotic 15 compounds, respectively, with improved bioactivity. DTS endeavors from our laboratory have uncovered new phenotypes for the antibiotic promysalin 16 and we sought to use our initial total synthesis of carolacton toward this end. We were inspired by the seminal work of Chandrasekhar et al in their disclosure of simplified pladienolide analogs wherein they rigidified the side chain with an aryl isostere and we determined that a similar replacement was feasible based on computational modeling (Figure 1).…”
mentioning
confidence: 99%